Force of Ice Cohesion with Some Metals (O Sile Stsepleniya lda s Nekotornyni Metallami) - Dolov,M. A.; Makuashev,M. K. (1971)
Based on an analysis of test data, it is established that: (1) force of ice cohesion with various materials depends on the type of material, condition of its surface and the temperature; (2) force of ice cohesion increases at a decrease in temperature and an increase in roughness of surface; and, (3) force of ice cohesion depends on ice structure and rate of increase of external load. The faster the rate of load increase, the greater the value of cohesion force. At gradual loading, the viscous-plastic properties of ice are manifested. (Author) Draft trans. of Vysokogornyi Geofizicheskii Institut, Nalchik. Trudy (USSR) n16 p118-123 1970.